Adaptive Model For Meeting Urban Forest Space Needs In Central Sulawesi - Akhbar, Hasriani Muis, Mahfudz, Golar, Adam Malik, Muhammad Fardhal Pratama, Rahmat Kurniadi Akhbar (International Journal of Advanced Science and Technology, 2020)
This study aims to develop a model for analysing urban forest space requirements based on demographic factors that visible in urban areas. The study adopts a spatial analysis approach, in addition to a general analysis of urban forest space requirements using the Malthus exponential method. From this analysis the value 8.90 m2/people set was obtained and subsequently, used as a reference for determining the area of urban forest space. From the value of this constant, a projection model for exponential growth in urban forest spaces in the urban area of Kolonodale (a small city with a population of ≤ 20,000 inhabitants) in the next 20 years: Yuf to-t = 9.7799